2016
DOI: 10.3109/10428194.2016.1160085
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating measurable (‘minimal’) residual disease-directed treatment strategies to optimize outcomes in adults with acute myeloid leukemia

Abstract: Curative-intent therapy leads to complete remissions in many adults with acute myeloid leukemia (AML), but relapse remains common. Numerous studies have unequivocally demonstrated that the persistence of measurable (“minimal”) residual disease (MRD) at the submicroscopic level during morphologic remission identifies patients at high risk of disease recurrence and short survival. This association has provided the impetus to customize anti-leukemia therapy based on MRD data, a strategy that is now routinely purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…One final notion is that we preferred here the recently developed concept of “measurable residual disease” to the classical “minimal residual disease,” keeping in mind that even “negative“ patients may relapse, indicating that we really have no clear idea of the minimal amount of disease remaining in the whole body. This may look merely semantic, but in our view, clarifies the limits of MRD measurement.…”
Section: Discussionmentioning
confidence: 99%
“…One final notion is that we preferred here the recently developed concept of “measurable residual disease” to the classical “minimal residual disease,” keeping in mind that even “negative“ patients may relapse, indicating that we really have no clear idea of the minimal amount of disease remaining in the whole body. This may look merely semantic, but in our view, clarifies the limits of MRD measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal changes in the antigen intensities and asynchronous relation of these markers allow identification of aberrancies based on the DfN approach. 27,35,44 It should also include lymphoid markers commonly expression on leukemic cells for the detection of LAIP such as CD7, CD19, CD56, etc. Other rarely expressed lymphoid markers can also be included in the panel to further increase the applicability, such as CD2, CD4, CD5, CD11b, CD25, etc.…”
Section: Selection Of Markersmentioning
confidence: 99%
“…25,29 However, several studies have suggested MRD levels below 0.1% can also reliably predict DFS and a few studies have also shown the predictive value of "any detectable level" for MRD positivity in AML. 2,11,16,19,20,24,26,29,33,42,44,50,52,57,60,66,68 The usual recommended MFC MRD assessment time points for BM samples are after two cycles of chemotherapy (postinduction), at the end of consolidation (postconsolidation), and before and at day 100 post-stem cell transplantation, if applicable. 24,25,[27][28][29]31,34,38,42,57,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] New Advances in MFC-MRD Currently, available data for MFC-MRD in AML are predominantly limited to 8-to 10-color flow cytometry assay that restricts the utility of combinations of different markers to existing 8-to 10-color antibody combinations limiting the number of LAIP or DfN approaches to few combinations.…”
Section: Clinically Significant Level Of Mrd and Time Pointsmentioning
confidence: 99%